Mesenchymal stem cells or extracellular vesicles in the choice of rheumatoid arthritis treatment - E. A. Takoeva; R. I. Kokaev; A. A. Islaev (Acta Biomedica Scientifica)
Background. Rheumatoid arthritis (RA) is a long-term autoimmune disease characterized by  a  systemic immuno-inflammatory reaction leading to  joint edema, synovial hyperplasia, damage to cartilage and bone tissue. There is currently no effective treatment for this disease.The aim of the literature review. To analyze the mechanisms described to date that underlie the effects of mesenchymal stem cells (MSC) and extracellular vesicles (EV) on the pathogenetic links of rheumatoid arthritis.Materials and methods. PubMed and eLibrary databases for the period 2011–2023 were analyzed using keywords: rheumatoid arthritis, hematopoietic stem cells, mesenchymal stem cells, rheumatoid factor, extracellular vesicles, cell therapy.Results and discussion. The  review describes current aspects of  the  etiology and pathogenesis of  rheumatoid arthritis, its potential biomarkers and currently known therapeutic strategies. The effect of MSC on T and B lymphocytes, as well as  other cellular participants in  the  disease, has been studied in  experimental and clinical studies. The  review expands the  understanding of  the  mechanisms of therapeutic effects of postnatal progenitor cells and their extracellular vesicles in  the  treatment of  rheumatoid arthritis, which, in  terms of  comparison, reveals the advantages and disadvantages of each method. It can be concluded that MSC and EV are a promising direction in the treatment of rheumatoid arthritis, however, further studies of the interactions of molecules affecting the links of the pathogenesis of RA are needed. Additional studies based on a pathogenetically ranked approach to the treatment of the disease are also necessary, which allows to identify the patterns of  effects of  each method with subsequent recommendation in  choosing the use of progenitor cells or, mainly, their secretome in personalized RA therapy, and a more detailed study of the dosage, time and method of their administration is also necessary.